2013
DOI: 10.1002/app.40145
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid sol gel coating: A solution to prevent interactions between plasticized poly(vinyl chloride) and injectable drugs?

Abstract: During the infusion of drugs with medical devices in plasticized poly(vinyl chloride) (PVC) release of plasticizers in the injectable solution and/or sorption of drugs on PVC may occur. Thus, patient safety and/or effectiveness of his therapy may be altered. In this study, we assessed the efficiency of a sol gel hybrid coating in preventing plasticizers' release (di-(2-ethylhexyl) phthalate (DEHP)) from PVC matrix and drug sorption into PVC. Remaining concentrations of drugs and plasticizer's concentration rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…These results are supported by Chellini et al, who demonstrated DEHP release from endoctracheal tubings in the early hours of intubation [24]. These data was confirmed by Bernard et al as part of a study to evaluate the efficiency of a protective PVC barrier against this release [20]. The method of administration of injectable drugs varies from one product to another and depends on the indication, the volume to be delivered, the product's nature, and the profile of the patient.…”
Section: The Contact Conditions Between the MD And The Fluid In A Clisupporting
confidence: 79%
See 1 more Smart Citation
“…These results are supported by Chellini et al, who demonstrated DEHP release from endoctracheal tubings in the early hours of intubation [24]. These data was confirmed by Bernard et al as part of a study to evaluate the efficiency of a protective PVC barrier against this release [20]. The method of administration of injectable drugs varies from one product to another and depends on the indication, the volume to be delivered, the product's nature, and the profile of the patient.…”
Section: The Contact Conditions Between the MD And The Fluid In A Clisupporting
confidence: 79%
“…The analysis of the drugs and products administered by injection enabled the distinction to be The data in the literature shows that the fatty nature of the solvents has a considerable influence on the extraction of the plasticizers from the PVC [16] [18], with a strength that is comparable to that of ethanol [19] [20], thus justifying its use as a simulant. In order to establish our models, it was therefore necessary to check the differences in lipid content of the identified drugs.…”
Section: Nature Of the Content In Contact With The MD Concernedmentioning
confidence: 99%
“…Nevertheless, these alternative plasticizers are still small molecular compounds and migration of plasticizers from soft PVC is unavoidable during long‐time service, which would result in decreasing of durability. Several strategies have been developed to reduce migration of small molecular plasticizers from flexible PVC, including surface crosslinking, surface grafting, surface coating, coextrusion, mixing with nano‐particles, internal plasticization, blending, and so forth. Blending with macromolecular plasticizers is one of the few solutions which combines practicability with effectiveness, due to its ease of manufacturing and nonmigratory nature of polymers.…”
Section: Introductionmentioning
confidence: 99%